ashwagandha supplementation (Withania somnifera dunal.): an integrative review - Riese, Flávia Graziela (2022)
Introduction: Ashwagandha (Withania somnifera Dunal.) has bioactive compounds that exert adaptogenic effects on the physiological system, helping the body to adapt to stress factors. However, few studies have been done bringing scientific data that show its effects on the improvement of sports performance. Objective: To identify the effects of Ashwagandha supplementation on the improvement of sports performance in athletes and non-athletes. Materials and methods: integrative literature review, using databases: Virtual Health Library, Academic Google, Scientific Electronic Library Online (SCIELO), U.S National Library of Medicine, National Institutes of Health (PUBMED). Publications were selected in the languages: Portuguese, English and Spanish, between the years 2011 to 2021 with descriptors in the three languages: “withania somnifera; ashwagandha; athletic performance; physical performance”. Eleven articles that addressed the guiding question were included, seven of which were randomized clinical trials, three systematic reviews with meta-analysis and a prospective clinical study. Results: In all included studies there was an improvement in the physical performance of athletes and non-athletes. Discussion: Increased VO2 max was the most relevant parameter, in addition to hematological alterations and stress management capacity. Unusual increase in appetite, libido, dizziness and indigestion were identified adverse effects. Doses ranged from 50 to 1250mg/day in the form of capsules and 2.5 to 12g of raw plant powder, with good tolerability. Conclusion: Ashwagandha is effective in improving physical performance, but studies are needed to assess the long-term effects of ingesting the plant in athletes and non-athletes.